2000
DOI: 10.1046/j.1365-2133.2000.03669.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of androgens in determining acne severity in adult women

Abstract: Our study suggests that the severity of acne manifestation in adult women is not determined by androgen production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
0
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 21 publications
(24 reference statements)
10
63
0
9
Order By: Relevance
“…8 Cibula et al demonstrated that, the severity of acne manifestation in adult women was not determined by androgen production and there must therefore be key factors other than androgen levels in the pathogenesis of acne. 6 In our study we found elevated serum testosterone in 7 (10%) cases and below normal level of serum testosterone was found among 13 (18.6%) of the control individuals. The difference between case and control was statistically significant (p<0.001).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…8 Cibula et al demonstrated that, the severity of acne manifestation in adult women was not determined by androgen production and there must therefore be key factors other than androgen levels in the pathogenesis of acne. 6 In our study we found elevated serum testosterone in 7 (10%) cases and below normal level of serum testosterone was found among 13 (18.6%) of the control individuals. The difference between case and control was statistically significant (p<0.001).…”
Section: Discussionmentioning
confidence: 65%
“…Their study suggests that the severity of acne manifestation in adult women is not determined by androgen production. 6 Held et al investigated the relationship between hyperandogenism and acne. Elevated serum androgen levels have been reported in patients with acne resistant to conventional dermatologic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Uso de cosméticos, alterações hormonais e nutricionais, coexistência de hirsutismo, dermatite seborreica, alopecia, irregularidade menstrual ou aspectos psicoevolutivos são elementos aventados na explicação dos diferentes padrões clínicos e de histó-ria natural da acne em diferentes grupos populacionais. 8,[11][12][13][14][15][16][17][18][19][20] Há carência de pesquisas epidemiológicas que comparem aspectos clínicos associados à acne feminina juvenil e adulta. O presente estudo objetiva analisar as características clínicas e epidemiológicas associadas às diferentes faixas etárias acometidas por acne nessa população.…”
Section: Introductionunclassified
“…30 It is not necessary to demonstrate androgen excess to achieve a benefit from antiandrogen therapy. Clinical observation suggests that deep-seated nodules on the lower face and neck are especially responsive to hormonal therapy.…”
Section: Hormonal Therapiesmentioning
confidence: 99%